A stitch in time…: Comparing late‐identified, late‐emerging and early‐identified dyslexia. (18th May 2022) - de Bree, Elise H.; van den Boer, Madelon; Toering, Boukje M.; de Jong, Peter F.
Abstract : When dyslexia is diagnosed late, the question is whether this is due to late‐ emerging (LE) or late‐ identified (LI) problems. In a random selection of dyslexia‐diagnosis case files we distinguished early‐diagnosed (Grade 1–3, n = 116) and late‐diagnosed (Grade 4–6) dyslexia. The late‐diagnosed files were divided into LE ( n = 54) and LI dyslexia ( n = 45). The LE group consisted of children whose national‐curriculum literacy outcomes did not warrant referral for dyslexia diagnosis in Grades 1–2; the LI group of children whose literacy outcomes did, but who were referred for diagnostic assessment after Grade 3. At the time of diagnosis, the percentage of poor performers on word‐level literacy measures generally did not differ between the groups. Only the LE group contained fewer poor performers than the early‐diagnosed and LI group on some word‐reading measures. All groups showed similar distributions of phonological difficulties. There were no indications of compensation through vocabulary, memory or IQ in either late‐diagnosed group. Our diagnosis‐based study confirms and extends previous research‐based studies on LE dyslexia. Moreover, it shows that LI dyslexia exists, which can be regarded as the existence of instructional casualties. The findings speak to issues of identification, diagnosis and compensation and call for further efforts to improve the early identification of dyslexia.